Three new species of Pachyrhynchus Germar 1824, (Coleoptera, Curculionidae, Entiminae) from Mindanao Island, The Philippines, with taxonomical notes - Bollino, Maurizio (Zootaxa, 2022)
Three new species of Pachyrhynchus Germar, 1824 are described from Mindanao Island, The Philippines: P. similis sp. nov., P. subanon sp. nov., and P. chrysomaculatus sp. nov. For each new taxon habitus photographs of male and female, and illustrations of male genitalia are provided. The author also proposes to consider the above species together with the closest ones as belonging to the new atrocyaneus species group.